1990
DOI: 10.1111/j.1471-6402.1990.tb00224.x
|View full text |Cite
|
Sign up to set email alerts
|

Women's Prime of Life: Is It the 50s?

Abstract: The hypothesis is advanced that the early 50s is women's prime of life, an androgynous time of good health combined with autonomy and relational security. In a sample of 700 college alumnae, aged 26–80, who were studied in 1983, women in their early 50s most often described their lives as “first‐rate.” In a longitudinal sample from the same institution in 1989, women in their early 50s also rated their quality of life as high. Conditions distinguishing the early 50s from earlier and/or later periods of the mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 25 publications
4
59
1
Order By: Relevance
“…For example, Erikson suggested that the maturity and superior functioning associated with midlife is linked to the "generativity" stage, during which individuals tend to be increasingly productive and creative at work, while at the same time promoting and guiding the next generation. Similarly, Mitchell and Helson (1990) described the latter part of midlife as a period characterized by higher levels of psychological maturity and adjustment and noted that during the postparental period "the energy that went to children is redirected to the partner, work, the community, or selfdevelopment" (p. 453). Role theories of aging suggest that over the course of adulthood individuals increasingly occupy positions of power and status, which might convey a sense of self-worth (Dannefer, 1984;Helson, Mitchell, & Moane, 1984;Hogan & Roberts, in press;Sarbin, 1964).…”
Section: What Have We Learned About the Development Of Self-esteem?mentioning
confidence: 99%
“…For example, Erikson suggested that the maturity and superior functioning associated with midlife is linked to the "generativity" stage, during which individuals tend to be increasingly productive and creative at work, while at the same time promoting and guiding the next generation. Similarly, Mitchell and Helson (1990) described the latter part of midlife as a period characterized by higher levels of psychological maturity and adjustment and noted that during the postparental period "the energy that went to children is redirected to the partner, work, the community, or selfdevelopment" (p. 453). Role theories of aging suggest that over the course of adulthood individuals increasingly occupy positions of power and status, which might convey a sense of self-worth (Dannefer, 1984;Helson, Mitchell, & Moane, 1984;Hogan & Roberts, in press;Sarbin, 1964).…”
Section: What Have We Learned About the Development Of Self-esteem?mentioning
confidence: 99%
“…Although considerable research suggests that menopause is experienced by many women as not particularly significant subjectively (see, e.g., Mitchell & Helson, 1990), it has nonetheless been examined extensively in terms of its expected implications for women's sexual desire, sexual attractiveness, and sexual activity, as well as women's self-esteem (Marshall & Katz, 2006;McHugh, 2007). Sometimes the findings have contradicted cultural stereotypes.…”
Section: Gender and Aging Bodiesmentioning
confidence: 97%
“…Midlife seems to constitute a key developmental stage for African American women and was therefore selected for examination in the study. These women are coping with a host of bio-psycho-social processes, and superimposed on these for African American women are the over arching factors of racism and politically sanctioned oppression (Larke, 1996;Westbrooks, 1995;hooks, 1992;Weed, 1992;Collins, 1990;Fodor, 1990;Mitchell & Helson, 1990;Giddings, 1984).…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…Midlife seems to constitute a key developmental stage for African American women and was therefore selected for examination in the study. These women are coping with a host of bio-psycho-social processes, and superimposed on these for African American women are the over arching factors of racism and politically sanctioned oppression (Larke, 1996;Westbrooks, 1995; hooks, 1992;Weed, 1992;Collins, 1990;Fodor, 1990;Mitchell & Helson, 1990; Giddings, 1984).Specifically, four research questions formed the basis for the current study:(1) Do African American women report differences in their levels of spirituality and their levels of religiosity?(2) As the aging process occurs do African American women become more spiritually connected? …”
mentioning
confidence: 99%